Atractylenolide III Attenuates Muscle Wasting in Chronic Kidney Disease via the Oxidative Stress-Mediated PI3K/AKT/mTOR Pathway. (18th April 2019) - Wang, Mingqing; Hu, Rong; Wang, Yanjing; Liu, Lingyu; You, Haiyan; Zhang, Jiaxing; Wu, Xiaohui; Pei, Tingting; Wang, Fujing; Lu, Lu; Xiao, Wei; Wei, Lianbo
Abstract : Oxidative stress contributes to muscle wasting in advanced chronic kidney disease (CKD) patients. Atractylenolide III (ATL-III), the major active constituent of Atractylodes rhizome, has been previously reported to function as an antioxidant. This study is aimed at investigating whether ATL-III has protective effects against CKD-induced muscle wasting by alleviating oxidative stress. The results showed that the levels of serum creatinine (SCr), blood urea nitrogen (BUN), and urinary protein significantly decreased in the ATL-III treatment group compared with the 5/6 nephrectomy (5/6 Nx) model group but were higher than those in the sham operation group. Skeletal muscle weight was increased, while inflammation was alleviated in the ATL-III administration group compared with the 5/6 Nx model group. ATL-III-treated rats also showed reduced dilation of the mitochondria, increased CAT, GSH-Px, and SOD activity, and decreased levels of MDA both in skeletal muscles and serum compared with 5/6 Nx model rats, suggesting that ATL-III alleviated mitochondrial damage and increased the activity of antioxidant enzymes, thus reducing the production of ROS. Furthermore, accumulated autophagosomes (APs) and autolysosomes (ALs) were reduced in the gastrocnemius (Gastroc) muscles of ATL-III-treated rats under transmission electron microscopy (TEM) together with the downregulation of LC3-II and upregulation of p62 according to Western blotting. This evidence indicated that ATL-III improved skeletal muscle atrophy and alleviated oxidative stress and autophagy in CKD rats. Furthermore, ATL-III could also increase the protein levels of p-PI3K, p-AKT, and p-mTOR in skeletal muscles in CKD rats. To further reveal the relevant mechanism, the oxidative stress-mediated PI3K/AKT/mTOR pathway was assessed, which showed that a reduced expression of p-PI3K, p-AKT, and p-mTOR in C2C12 myoblast atrophy induced by TNF- α could be upregulated by ATL-III; however, after the overexpression of Nox2 to increase ROS production, the attenuated effect was reversed. Our findings indicated that ATL-III is a potentially protective drug against muscle wasting via activation of the oxidative stress-mediated PI3K/AKT/mTOR pathway.